Role of Rural Libraries in Rural Areas - Kunhambu, K.; Mudhol, Mahesh V. (Journal of Information and Knowledge, 2012)
Education plays a vital role in the overall development of an individual. Public library should be a living force behind it. It should cover all sections of society including the illiterate, neo-literate, semi-skilled, children and youth, house-wives etc. Library should create reading habits among the rural people through distribution of books, display of attractive pictures etc. In India, rural population‟s economic needs are very much related to small enterprises and agriculture. The material should be related to better farming techniques, new seed technology, pesticides, good health family planning programmes, cultural values, small savings and other activities related to social evils which will fulfill the purpose of rural libraries. Lack of education is a huge problem for the developing world, and literacy and information literacy just have to be promoted. Therefore rural libraries and school libraries should be main targets for aid from developing countries in order to create a situation where the developing countries could reach the ability to help themselves.